1998
DOI: 10.1046/j.1365-3040.1998.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modelling environmental influences on photosynthetic gas exchange in Sphagnum and Pleurozium

Abstract: A mechanistic model has been used to examine the environmental regulation of photosynthetic gas exchange in moss. The effects of water content on conductance to CO 2 and on photosynthetic capacity during desiccation were calculated from the carbon isotope discrimination data of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 22 publications
12
146
0
Order By: Relevance
“…Under non-irradiation-limited conditions, the photosynthesis of C3 plants and mosses is considered to correlate approximately linearly with the ambient CO 2 concentration at CO 2 concentrations between 300 ppm and 400 ppm. This has been shown by several previous studies (Morison and Gifford, 1983;Grulke et al, 1990;Stitt, 1991;Sage, 1994;Luo and Mooney, 1996;Williams and Flanagan, 1998;Griffin and Luo, 1999). Consequently, F P (t) can be modelled for periods with nonirradiation-limited photosynthesis of a canopy consisting of C3 plants and/or mosses, which is typical for tundra and peatlands, as:…”
Section: Development Of the Nonlinear Exponential Modelmentioning
confidence: 69%
“…Under non-irradiation-limited conditions, the photosynthesis of C3 plants and mosses is considered to correlate approximately linearly with the ambient CO 2 concentration at CO 2 concentrations between 300 ppm and 400 ppm. This has been shown by several previous studies (Morison and Gifford, 1983;Grulke et al, 1990;Stitt, 1991;Sage, 1994;Luo and Mooney, 1996;Williams and Flanagan, 1998;Griffin and Luo, 1999). Consequently, F P (t) can be modelled for periods with nonirradiation-limited photosynthesis of a canopy consisting of C3 plants and/or mosses, which is typical for tundra and peatlands, as:…”
Section: Development Of the Nonlinear Exponential Modelmentioning
confidence: 69%
“…i assumed based on literature (Givnish, 2002;Reich et al, 1998) so that V max values are higher in evergreens than in deciduous and are in line with the values for trees. j V max of mosses is 14 in the summer and 6.5 in the remaining time (Williams and Flanagan, 1998).…”
Section: Heterotrophic Respirationmentioning
confidence: 98%
“…Williams and Flanagan, 1998;Robroek et al, 2009). In CLASS, evaporation at the soil surface is controlled by a soil evaporation efficiency coefficient β .…”
Section: Soil Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum rate of carboxylation (V cmax ) typically varies across peat sites (Rennermalm et al, 2005;Bubier et al, 2011) and further varies with leaf nitrogen, phosphorus content, and specific leaf area (Wright et al, 2004;Walker et al, 2014). For instance, V cmax for Sphagnum at the Old Black Spruce site (53.985 • N, 105.12 • W) in Canada was 5, 14, and 6 µmol m −2 s −1 during spring, summer, and autumn, respectively, while V cmax for Pleurozium was 7, 5, and 7 µmol m −2 s −1 during the three seasons (Williams and Flanagan, 1998). Bui (2013) conducted a fertilization experiment at the Mer Bleue Bog (Canada; 45.41 • N, 75.52 • W) on the dominant ericaceous shrub and reported that V cmax values ranged between 6 and 179 µmol m −2 s −1 , with significantly higher V cmax values after addition of nitrogen (6.4 g N m −2 yr −1 ) at 20 times the growing season ambient wet N deposition rate with or without phosphorus (P) and potassium (K).…”
Section: Modified Peat Plant Parametersmentioning
confidence: 99%